Does r-g cause wealth inequality? The case of the United States - Strauss, David; Ventosa-Santaularia, Daniel (Estudios Económicos de El Colegio de México, 2023)
Piketty claims that the gap between the return to capital and the growth rate (r−g) governs the evolution of wealth inequality. This paper assesses its empirical validity using an IV approach and almost one century of US data. Our results are twofold: First, wealth shares are nonstationary, necessitating first differences to draw a valid inference from any econometric exercise. This is consistent with Piketty’s line of argumentation and casts doubt on studies on inequality that use inequality levels without showing the trending behavior of the data. Second, r−g played a significant role in the evolution of wealth inequality over the last century, both statistically and economically. In particular, r−g can explain over 50% of the increase in wealth inequality since the late 1970s.